AUDIT SISTEM INFORMASI STOK PADA APLIKASI SAP MENGGUNAKAN MODEL COBIT FRAMEWORK 4.1 PADA PT SEMANGAT SEJAHTERA BERSAMA (PT SSB) - Aliffah Kusumaningrum; Andi Rosano; Nur Ali Farabi; Feggy Agus Setiawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
The development of technology today is very advanced. In every field, it is very much in need of technology, especially information system technology. This must be balanced with the existence of an information system audit so that losses can be reduced. This study aims to determine the stock information system audit at PT.Semangat Sejahtera Bersama and Cobit 4.1 framework is only as a liaison between the stock information system audit. PT. SSB has implemented a stock information system at the Defined Process level. The results of processing the questionnaire found the average value for the PO and ME domains was 2.55 from the range of values ​​from 0 to 5. PT. SSB has implemented a good stock information system. From the results of the study found weaknesses in the PO6 sub-domain with an average value of 2.31 meaning that it is still at level 2 - Repeatable but Intuitive. The most fatal weakness is that the company has not been able to develop and maintain a framework that defines the company's overall approach to risk and which is in line with the stock information system, company risk and control framework environmental policies.